2020
DOI: 10.12968/jowc.2020.29.sup5a.s9
|View full text |Cite
|
Sign up to set email alerts
|

Barbed and conventional sutures in spinal surgery patients: an economic and clinical outcomes comparison

Abstract: Objective: To compare economic and clinical outcomes of barbed sutures versus conventional sutures alone in wound closure for patients undergoing spinal surgery. Method: A retrospective study using the Premier Healthcare Database. The database was searched for patients who underwent elective inpatient spinal surgery (fusion or laminectomy) for a spinal disorder between 1 January 2014 and 30 June 2018 (first=index admission). Using billing records for medical supplies used during the index admission, patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Our results indicated significant lower ORT when incorporating barbed sutures, suggesting clinical efficiency of using barbed sutures in posterior long-segment lumbar surgery as overall ORT was measured as an efficiency outcome, consistent with previous findings [ 9 , 12 ]. Additionally, our findings revealed that applying barded sutures cost significantly shorter time than the traditional sutures both in the entire wound closure procedure (17.24 min difference, P < 0.001) and wound closure for per centimeter of incision (1.04 min difference, P < .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results indicated significant lower ORT when incorporating barbed sutures, suggesting clinical efficiency of using barbed sutures in posterior long-segment lumbar surgery as overall ORT was measured as an efficiency outcome, consistent with previous findings [ 9 , 12 ]. Additionally, our findings revealed that applying barded sutures cost significantly shorter time than the traditional sutures both in the entire wound closure procedure (17.24 min difference, P < 0.001) and wound closure for per centimeter of incision (1.04 min difference, P < .…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it has been a critical wound complication that deserves special attention in spinal surgeries. In earlier studies, no statistical differences in wound infection rates were reported between the barbed sutures and conventional sutures groups [ 9 , 15 ]. However, our results yielded disparate outcomes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite barbed sutures being more expensive than its conventional counterparts 10 , three studies have shown that the use of barbed sutures reduced the time in the operating room in patients who have undergone spinal surgery 20 and total knee arthroplasty 21,22 . The same studies reported that the reduction in the time spent in the operating room was associated with a decrease in the final cost of the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Previous studies have reported that using the barbed sutures to close incision in a variety of surgeries was related to a reduction of wound complications and operation time in various surgeries. [ 12 , 13 ] Despite all potential advantages, barbed suture is not commonly used in TKR. This might be due to its higher cost and uncertain clinical benefits.…”
Section: Introductionmentioning
confidence: 99%